Ultra‐Stable and High‐Cobalt‐Loaded Cobalt@Ordered Mesoporous Carbon Catalysts: All‐in‐One Deoxygenation of Ketone into Alkylbenzene. Issue 15 (30th May 2018) - Zhang, Pengfei; Chen, Nanqing; Chen, Dong; Yang, Shize; Liu, Xiaofei; Wang, Li; Wu, Peiwen; Phillip, Nathan; Yang, Guang; Dai, Sheng
Abstract: Catalytic deoxygenation represents a straightforward and core methodology for fine‐chemical production and biomass upgrading. Generally, the application of homogeneous metal complexes or heterogeneous noble‐metal catalysts prevails in academia and the chemical industry. Herein, we introduce cobalt@ordered mesoporous carbon (Co@OMC) catalysts, which are constructed conveniently by a mechanochemical coordination self‐assembly based on a renewable tannin precursor. Importantly, the Co@OMC catalysts with a high loading of in situ confined Co species promote the selective deoxygenation of various ketones, aldehydes, and alcohols efficiently into the corresponding alkanes under mild conditions. Therefore, a simple, inexpensive, and heterogeneous catalyst for selective deoxygenation can be expected, meanwhile the solid‐state synthesis affords a green, rapid, and scalable pathway to Co@OMC catalysts. Abstract : All‐in‐one catalysis : A mechanochemical self‐assembly method is developed to prepare cobalt@ordered mesoporous carbon directly that does not need any solvents and can be completed in 60 min. This strategy enables a high loading of Co nanoparticles to be confined inside ordered mesoporous channels. Those Co catalysts possess a good stability and activity in the selective deoxygenation of ketones, aldehydes, and alcohols.